Investigation of Students' Difficulties in Mathematical Language : Problem-Solving in Mathematical Word Problems at Elementary Schools - Agusfianuddin Agusfianuddin; Tatang Herman; Turmudi Turmudi (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research investigates students' mathematical language difficulties in solving word problems in elementary school. This research method uses a descriptive with a qualitative approach. The research subjects were 52 fifth-grade elementary school students using a purposive sampling technique with students of different abilities, namely upper, middle and lower abilities. Data collection techniques included triangulation data sources through tests, interviews, and questionnaires, as well as data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Research findings show that students with upper and middle ability problem solving are in the